2022
DOI: 10.1038/s41598-022-11225-5
|View full text |Cite
|
Sign up to set email alerts
|

Between-hospital variations in 3-year survival among patients with newly diagnosed gastric, colorectal, and lung cancer

Abstract: Due to increases in cancer survivability, quality assessments of cancer care must include long-term outcomes. This multicenter retrospective cohort study evaluated between-hospital variations in the 3-year survival rates of patients with gastric, colorectal, and lung cancer irrespective of treatment modality. We linked cancer registry data and administrative data from patients aged 18–99 years who were diagnosed with gastric, colorectal, or lung cancer between 2013 and 2015 in Osaka Prefecture, Japan. The 3-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In addition to whether women had a preexisting SMI, we adjusted for other variables that may influence cancer care pathways, including socioeconomic status, overall health state, and characteristics of the hospital where care was received, which may influence treatment choice and mortality [ 54 , 55 , 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to whether women had a preexisting SMI, we adjusted for other variables that may influence cancer care pathways, including socioeconomic status, overall health state, and characteristics of the hospital where care was received, which may influence treatment choice and mortality [ 54 , 55 , 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, clinical data from a hospital-based cancer registry were linked with administrative data produced by hospitals for reimbursements under Japan's Diagnosis Procedure Combination/Per-Diem Payment System. The details of this record-linked database have been reported previously [19][20][21][22][23][24][25][26]. Briefly, the hospital-based cancer registry collects patient demographic information, as well as information on the diagnosis and treatment of newly diagnosed cancer cases; this includes the date of diagnosis, topographical and morphological codes based on the International Classification of Diseases for Oncology Third Edition (ICD-O-3), cancer stage at the time of diagnosis based on the Seventh Edition of the Union for International Cancer Control staging system, and cancer treatment modality.…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…Recent studies demonstrated that patients who underwent surgery at the national or prefectural ACHs had higher 3-year survival than their counterparts who were treated at nondesignated hospitals, 21 and that survival rates of patients with common solid cancers did not differ across ACHs after adjusting for case mix. 22 While several studies support the effectiveness of the current cancer control measures in improving populationlevel survival, 21,22 it remains understudied as to whether such measures could also address the existing socioeconomic disparities in cancer care and survival. In light of the above, the objectives of the present study are to (1) describe socioeconomic disparities and their trends in cancer care and survival, and (2) examine the extent to which socioeconomic disparities in cancer survival are explained by factors that are relevant to cancer control measures (i.e., promoting early-stage detection, standardizing treatment, and centralizing patients to ACHs) in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that patients who underwent surgery at the national or prefectural ACHs had higher 3‐year survival than their counterparts who were treated at non‐designated hospitals, 21 and that survival rates of patients with common solid cancers did not differ across ACHs after adjusting for case mix. 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation